Training distribution, physiological profile, and performance for a male international 1500-m runner - Ingham, S. A.; Fudge, B. W.; Pringle, J. S. (International Journal of Sports Physiology and Performance, 2012)
This case study observed the training delivered by a 1500-m runner and the physiological and performance change during a 2-y period. A male international 1500-m runner (personal best 3:38.9 min:s, age 26 y, height 1.86 m, body mass 76 kg) completed 6 laboratory tests and 14 monitored training sessions, during 2 training years. Training distribution and volume was ascertained from training diary and spot-check monitoring of heart rate and accelerometry measurements. Testing and training information were discussed with coach and athlete from which training changes were made. In the first training year, low-intensity training was found to be performed above the prescribed level, which was adjusted with training and coach support in y 2 (training zone < 80% of vVO2max, y 1 = 20%; y 2 = 55%). "Tempo" training was also performed at an excessively high intensity (delta [blood lactate] 5-25 min of tempo run, y 1 = delta6.7 mM, y 2 = delta 2.5 mM). From y 1 to 2, there was a concomitant increase in the proportion of training in the high-intensity zone of 100 to 130% vVO2max from 7 to 10%. Values for VO2max increased from 72 to 79 mL/kg·min, economy improved from 210 to 206 mL/kg·min, and 1500-m performance time improved from 3:38.9 to 3:32.4 min:s from the beginning of y 1 to the end of y 2. This case shows a modification in training methodology that was coincident with a greater improvement in physiological capability and furtherance in performance improvement.